The soils of Italy - Dazzi, Carmelo; Costantini, Edoardo A.C (World Soils Book Series,, 2013)
The Soils of Italy is the first comprehensive book on Italian pedology in seventy years. Taking advantage of the authors' large experience and of the most up-to-date  information and technology, this book treats the main soil types of Italy, their diffusion, their functions, ecological use, and the threats to which they are subjected during centuries of intensive management. It also deals with future scenarios of the relationships between soil science and other disciplines, such as urban development, medicine, economics, sociology, and archaeology. The description of the soils is accompanied by a complete set of data, pictures and maps, including benchmark profiles. Factors of soil formation are also treated, making use of new, unpublished data and elaborations. The book also includes a history of pedological research in Italy, spanning over a century.